Effects of Alendronate and Raloxifene on Bone Density and Bone Turnover Markers in Postmenopausal Women - Ebru Zülfikaroğlu; Sevtap Kılıç; Süleyman Eserdağ; Sertaç Batıoğlu (Medical Network, 2011)
OBJECTIVE: The aim of this study was to compare the effects of once weekly alendronate sodium (ALN) and daily raloxifene hydrochloride (RLX) treatment on bone mineral density (BMD) and bone turnover markers in postmenopausal osteoporotic women. STUDY DESIGN: We included 343 postmenopausal women with osteoporosis (femoral neck BMD Tscore, less than -2.5), but 286 (83.4%) completed the study. Women (aged ≤75 yr; ≥2 yr since their last menstrual period) randomly classified into three groups. Group 1 (n=96) received ALN (70mg/week) and group 2 (n=95) received RLX (60 mg/day) and group 3 (n=95) received placebo. The efficacy of treatment was evaluated by BMD measurements at spine and hip, as well as by the measurement of bone turnover markers such as bone specific alkaline phosphatase (BSAP) and urine dehydroxyproline (DOHP) at baseline, 6th and 12th months. RESULTS: The evaluation of the changes in BMD and bone markers at 12 months were different between the placebo and each of the active treatment groups (P<0.05). The increase in BMD at 1 yr in ALN group was significantly greater than RLX group. The 4.5% increase in lumbar spine BMD with ALN was different from the 2% increase in RLX group (P<0.001). The 2.6 % increase in femoral neck BMD with ALN was different from the 1.8% increase in the RLX group (P=0.03). The biochemical markers of bone turnover D-OHP and BSAP in both treatment groups decreased from baseline and were different from placebo at 1 year. The decreases in D-OHP and BSAP were approximately 2.1 fold greater in the ALN group. The decreases were significantly greater in ALN group than in RLX group (P<0.001). CONCLUSION: ALN 70 mg once- weekly significantly produced greater increases in spine and greater but not significantly increases in hip BMD and significantly greater reductions in markers of bone turnover than RLX in 1 yr treatment period. Both ALN and RLX treatment groups have similar safety and tolerability profiles.